Three concepts of history - Campillo, Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The aim of this article is twofold. On the one hand, I will outline the diverse usages that the concept of history has taken on throughout Western history. These different usages may be grouped together in three semantic fields (history as a way of knowing, as a way of being and as a way of doing), which correspond to three ways of understanding the Philosophy of History: as Epistemology of History, as Ontology of historicity and as ethical-political Critique of the present. On the other hand, I will show that these three concepts of history (and, accordingly, the three ways of understanding the Philosophy of History) refer mutually to each other and, thus, are inseparable from each other.
Keywords: history; philosophy; science; Time; action